The Role of Current Family Relationships in Associations Between Childhood Abuse and Adult Psychological Functioning. (19th June 2018) - Kong, Jooyoung; Moorman, Sara M; Martire, Lynn M; Almeida, David M
Abstract: Objectives: Childhood abuse has long-term negative effects on adult psychological well-being. This study examined whether and how adults with a history of childhood abuse may experience poor psychological functioning partly due to aspects of current family relationships. Method: We estimated multilevel mediation models using 3 waves of longitudinal data from 3, 487 participants in the study of Midlife Development in the United States. Outcomes measured included negative affect, life satisfaction, and psychological well-being. We included aspects of family relationships as mediators: perceived support, perceived strain, frequency of contact, and hours of providing instrumental and emotional support. Results: Multilevel mediation models showed that childhood verbal and physical abuse negatively affected diverse aspects of family relationships in later adulthood (i.e., less perceived support, more perceived strain, less frequent contact, and fewer hours of providing instrumental support). We also found that less perceived support and more family strain significantly mediated the associations between childhood abuse and all 3 psychological functioning outcomes. Discussion: Childhood abuse appears to hinder perceived availability of family support in adulthood, which may undermine the psychological functioning of adults with a history of childhood abuse. To improve their psychological health, interventions should focus on facilitating supportive and functional family relationships.